2005
DOI: 10.1124/jpet.105.095505
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E-Derived Peptides Block α7 Neuronal Nicotinic Acetylcholine Receptors Expressed inXenopusOocytes

Abstract: For decades, the pathology of Alzheimer's disease has been associated with dysfunction of cholinergic signaling; however, the cellular mechanisms by which nicotinic acetylcholine receptor (nAChR) function is impaired in Alzheimer's disease are as yet unknown. The most significant genetic risk factor for the development of Alzheimer's disease is inheritance of the ⑀4 allele of apolipoprotein E (apoE). Recent data have demonstrated the ability of apoE-derived peptides to inhibit nAChRs in rat hippocampus. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 39 publications
3
31
0
Order By: Relevance
“…As previously reported (Gay et al, 2006), the eight-aminoacid peptide apoE 141-148 (3 M, near maximal inhibition) significantly reduced the amplitude of wild-type ␣7 nAChR-mediated responses by 78 Ϯ 3% (Table 1, Fig. 2A).…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…As previously reported (Gay et al, 2006), the eight-aminoacid peptide apoE 141-148 (3 M, near maximal inhibition) significantly reduced the amplitude of wild-type ␣7 nAChR-mediated responses by 78 Ϯ 3% (Table 1, Fig. 2A).…”
Section: Resultssupporting
confidence: 60%
“…Previous studies indicated that a synthetic apoE peptide, containing the low-density lipoprotein receptor binding region, can inhibit ␣7 nAChR-mediated ACh-induced currents through a direct interaction. In addition, previous functional data suggest that this peptide/receptor interaction is noncompetitive with ␣-BgTx blockade and possibly ACh gating of the receptor (Gay et al, 2006). Direct binding experiments using ␣-BgTx were carried out to determine whether apoE 141-148 binds competitively with the toxin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An APOE-derived peptide blocks nAChRs on rat hippocampal slices with a submicromolar affinity, and this action is dependent on an arginine-rich segment of the APOE peptide (Klein and Yakel, 2004). Block of heterologously expressed ␣7 nAChRs is greater than that for ␣4␤2 or ␣2␤2 nAChRs (Gay et al, 2006). This block of ␣7 receptors is abolished when ␣7 Trp55 is mutated to alanine, providing strong evidence that it results from a direct interaction between the peptide and the receptors (Gay et al, 2007), and the effects of other substitutions of Trp55 suggests that this interaction is hydrophobic.…”
Section: E Apolipoprotein E-4 the Product Of An Alzheimer's Diseasementioning
confidence: 99%